(untitled) (Journal of Engineering, 2009)
The paper presents properties of high performance concrete reinforced with relatively high percentage of choped carbon fibers vol. fraction ranging from (1 to 5) %. The great advantage of such composites is their relatively high flexural strength. A low water to cement ratio of 0.3 with super plasticizer was used in order to keep the cement mix easily workable. To improve the properties, a locally existing pozzolan based on reactive meta- kaolin was used in the mixture together with silica sand. A high modulus carbon fibers (450 KN/mm2) were also used. In addition to the flexural strength, dynamic modulus of elastisity were found using dynamic methods. The results showed that the specimen failed in flexureal by a single crack although the ultimate tensile strength and the stiffness of the composite were increased as the fibers content was increased.